Scaling up and Improving Insurance Schemes for Farmers in India and Nigeria - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Establishing well-designed insurance schemes in agriculture not only enhances resilience when climatic shocks occur, the presence of a safety net can help farmers overcome the risk of investing in climate-smart technologies. In India, 12 million farmers are already insured through weather-index schemes. However, reports indicate that many farmers are unsatisfied with the current schemes due to prevalent basis risk, which occurs when the index measurements do not line up with the insured person’s actual losses. Basis risk can be avoided through proper insurance scheme design and accurate measurements. CCAFS analysed the current index insurance scheme in India, and found that the insurance triggers were insufficient. Using various scientific techniques to analyse crop-weather relationships, CCAFS developed new triggers, specific to different regions and crops, without increasing premiums and the government subsidy load. Maharashtra state has already adopted these new products, as well as the Agricultural Insurance Company of India, providing improved rainfall risk coverage to nearly one million farmers.